2018
DOI: 10.1111/odi.12789
|View full text |Cite
|
Sign up to set email alerts
|

Tissue eosinophilia in oral intraepithelial neoplasia as a probable indicator of invasion

Abstract: Our results suggest that eosinophils can be considered an indicator of invasion in OIN, helping in cases of difficult diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The prognostic value of 172 protein biomarkers was evaluated by immunohistochemistry in 174 studies (Table 2). These markers are classified according to their biological functions, mainly including such functional pathways as EMT and metastasis [59][60][61][62][63][64][65][66][67][68][69][70][71], inflammation and immunity [72][73][74][75][76][77][78][79][80][81][82][83][84], antioxidant [85,86], angiogenesis [87][88][89][90][91][92][93][94][95][96][97][98][99], cell proliferation, migration and invasion [100][101][102][103][104]…”
Section: Tissue-based Prognostic Biomarkersmentioning
confidence: 99%
“…The prognostic value of 172 protein biomarkers was evaluated by immunohistochemistry in 174 studies (Table 2). These markers are classified according to their biological functions, mainly including such functional pathways as EMT and metastasis [59][60][61][62][63][64][65][66][67][68][69][70][71], inflammation and immunity [72][73][74][75][76][77][78][79][80][81][82][83][84], antioxidant [85,86], angiogenesis [87][88][89][90][91][92][93][94][95][96][97][98][99], cell proliferation, migration and invasion [100][101][102][103][104]…”
Section: Tissue-based Prognostic Biomarkersmentioning
confidence: 99%
“…The predominant findings from these studies indicate that a finding of higher eosinophil infiltration in pre-malignant lesions should prompt a detailed investigation to rule out the invasion. Researchers have also suggested that TEC may be used as an adjunct tool in cases of suspected malignant transformation in oral leukoplakia with dysplastic changes [68,69,71]. Furthermore, an interesting study by Reddy et al revealed that, among 30 cases of oral submucosal fibrosis, 57% exhibited peripheral blood eosinophilia [106].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this theory, tumour-associated tissue eosinophilia (TATE) and tumour-associated blood eosinophilia (TABE) were identified in one study to be independent prognostic markers for premalignant and malignant OSCC, with elevated tissue eosinophils correlating with a favourable pre-malignancy prognosis, i.e., leukoplakia followed by dysplasia, respectively, while TABE was associated with poor prognosis [70]. Moreover, eosinophils may be considered as an indicator of invasion in oral intraepithelial neoplasia (OIN), and their presence may assist in cases of difficult diagnosis [71]. ↑ TABE is a poor prognosis in high-grade OSCC.…”
Section: Role Of Eosinophils In Oral Precancerous Lesionsmentioning
confidence: 99%
“…Another drawback was that the authors described the eosinophils as mononuclear cells with eosinophilic granular cytoplasm (10). In addition to other studies describing quantification of eosinophils in OSCC that was also limited by the subjective counting of the cells (27)(28)(29)(30).The current work provides a digital non subjective method of quantification and confirms that the auto-fluorescent cells are bi-nucleated with granular cytoplasm, that was confirmed on the H&E stained serial section as bi-nucleated cells with granular eosinophilic cytoplasm.…”
Section: Discussionmentioning
confidence: 99%